Local Action Groups as an Example of Participation and Development of Community: the Case of “Moravian Way” Local Action Group - Markéta Zapletalová; Pavel Šaradín (Journal of Deliberative Democracy)
The main goal of this article is to present local action groups in the Czech Republic as participative and deliberative platforms offering a unique environment for citizen participation as well as other actors (representatives of public and local administration, NGOs, and local business interests) functioning as leaders of territorial development. The paper explores the specific case of the Moravian Way Local Action Group, describing and explaining the participative and deliberative tools used to create and subsequently evaluate territory-based strategies. This case demonstrates that the use of these forms leads to the successful development of the territory. The focus on deliberative tools and the participative behaviour of different sets of territorial actors adds an important new perspective to the evaluation of innovative participative processes on the local level.